Hydrogels Derivatized With Cationic Moieties or Functional Peptides as Efficient Supports for Neural Stem Cells - Glotzbach, Kristin; Stamm, Nils; Weberskirch, Ralf; Faissner, Andreas (Frontiers in Neuroscience, 2020)
The increasing incidence of neurodegenerative diseases such as Alzheimer’s or Parkinson’s disease represents a significant burden for patients and national health systems. The conditions are primarily caused by the death of neurons and other neural cell types. One important aim of current stem cell research is to find a way to replace the lost cells. In this perspective, neural stem cells (NSCs) have been considered as a promising tool in the field of regenerative medicine. The behavior of NSCs is modulated by environmental influences, for example hormones, growth factors, cytokines, and extracellular matrix molecules or biomechanics. These factors can be studied by using well-defined hydrogels, which are polymeric networks of synthetic or natural origin with the ability to swell in water. These gels can be modified with a variety of molecules and optimized with regard to their mechanical properties to mimic the natural extracellular environment. In particular modifications applying distinct units such as functional domains and peptides can modulate the development of NSCs with regard to proliferation, differentiation and migration. One well-known peptide sequence that affects the behavior of NSCs is the integrin recognition sequence RGD that has originally been derived from fibronectin. In the present review we provide an overview concerning the applications of modified hydrogels with an emphasis on synthetic hydrogels based on poly(acrylamides), as modified with either cationic moieties or the peptide sequence RGD. This knowledge might be used in tissue engineering and regenerative medicine for the therapy of spinal cord injuries, neurodegenerative diseases and traumata.